A Foreign Language Anxiety Scale for Hungarian Learners of English - Tóth, Zsuzsa (Working Papers in Language Pedagogy, 2008)
This paper reports on the adaptation of a well-established foreign language anxiety scale for use in the Hungarian EFL setting; furthermore, the validation procedures aimed at testing the psychometric properties of the new instrument. Horwitz, Horwitz and Cope’s (1986) Foreign Language Classroom Anxiety Scale (FLCAS) was adapted using the method of multiple translators and back translation, and the Hungarian version of the scale (HFLCAS) was tested for response validity. The HFLCAS was administered to 117 English major and 66 non-English major students, whose responses were factor-analysed to test the scale’s construct validity. Reliability was assessed using the internal consistency method. The Hungarian FLCAS has been shown to be both reliable and valid in terms of the examined criteria. The results of factor analysis support Horwitz et al.’s (1986) theoretical foreign language anxiety (FLA) construct, hitherto unexamined in the Hungarian EFL context.